Human Tissue-Engineered Skeletal Muscle: A Tool for Metabolic Research - 김지훈; 유승민; 손장원 (대한내분비학회, 2022)
Skeletal muscle is now regarded as an endocrine organ based on its secretion of myokines and exerkines, which, in response to metabolic stimuli, regulate the crosstalk between the skeletal muscle and other metabolic organs in terms of systemic energy homeostasis. This conceptual basis of skeletal muscle as a metabolically active organ has provided insights into the potential role of physical inactivity and conditions altering muscle quality and quantity in the development of multiple metabolic disorders, including insulin resistance, obesity, and diabetes. Therefore, it is important to understand human muscle physiology more deeply in relation to the pathophysiology of metabolic diseases. Since monolayer cell lines or animal models used in conventional research differ from the pathophysiological features of the human body, there is increasing need for more physiologically relevant in vitro models of human skeletal muscle. Here, we introduce recent studies on in vitro models of human skeletal muscle generated from adult myogenic progenitors or pluripotent stem cells and summarize recent progress in the development of three-dimensional (3D) bioartificial muscle,which mimics the physiological complexity of native skeletal muscle tissue in terms of maturation and functionality. We then discussthe future of skeletal muscle 3D-organoid culture technology in the field of metabolic research for studying pathological mechanisms and developing personalized therapeutic strategies.